A stochastic RNA editing process targets a select number of sites in individual Drosophila glutamatergic motoneurons. - Crane, A.B.; Inouye, M.O.; Jetti, S.K.; Littleton, J.T. (eLife, 2025)
RNA editing is a post-transcriptional source of protein diversity and occurs across the animal kingdom. Given the complete profile of mRNA targets and their editing rate in individual cells is unclear, single-cell RNA transcriptomes obtained by Patch-seq from Drosophila larval glutamatergic motoneuron subtypes were analyzed to determine the most highly edited targets and identify single neuron editing rules. 316 high-confidence A-to-I canonical RNA edit sites were identified, with 60 causing missense amino acid changes predicted to alter proteins regulating membrane excitability, synaptic transmission, or neuronal function. Twenty-seven canonical sites were edited at >90% frequency as observed for editing of mammalian AMPA receptors. However, most sites were edited at lower levels and generated variable expression of edited and unedited mRNAs, suggesting stochastic editing that may provide a mechanism to fine-tune synaptic function similar to alternative splicing. Noncanonical editing was also found to occur in these neurons, including a C-to-U edit that altered an amino acid in the capsid hinge domain of the synaptic plasticity regulator Arc1. Together, these data provide insights into how the RNA editing landscape may alter protein function to modulate the properties of two well-characterized neuronal populations in Drosophila.